HUBUNGAN PENGETAHUAN TENTANG VAKSIN COVID-19 DENGAN KECEMASAN PADA MASYARAKAT DI DESA KALAIT MINAHASA TENGGARA - Engryne Nindi , Michelle Kairupan (JURNAL ILMIAH KESEHATAN MANADO, 2022)
Michelle Kairupan1Engryne Nindi2 Email : michellekairupan30@gmail.com engryne@gmail.com Pemerintah Indonesia sudah menyatakan pandemik COVID-19 sebagai bencana nasional non alam, dan sebagai upaya pencegahan penyebaran virus ini, pemerintah memberlakukan beberapa kebijakan, seperti pembatasan aktivitas keluar rumah, mewajibkan pelaksanaan pekerjaan dan pembelajaran daring, dan menghentikan kegiatan beribadah massal. Kecemasan merupakan hal umum yang sering terjadi untuk merespon perubahan lingkungan atau kejadian yang menyusahkan. Tujuan penelitian ini Teranalisis Hubungan Pengetahuan Tentang Vaksin Covid-19 Dengan Kecemasan Pada Masyarakat di Desa Kalait Minahasa Tenggara. Jenis penelitian yang digunakan dalam penelitian ini adalah deskriptif analitik dengan pendekatan cross sectional study. Populasi dalam penelitian ini adalah masyarakat yang berumur 18-59 dengan sampel berjumlah 55 responden. Data dianalisa dengan menggunakan uji statistik chi square dengan tingkat kemaknaan (α) : 0,05. Berdasarkan hasil uji statistik didpatkan nilai p value 0,002 lebih kecil dari 0,05 maka Ha diterima sehingga ada hubungan pngetahuan tentang vaksin covid-19 dengan kecemasan pada masyarakat di Desa Kalait Minahasa Tenggara. Pada penelitian ini odds ratio 7,071 yang artinya pengetahuan yang kurang baik mempunyai peluang 7 kali untuk mengalami kecemasan terkait vaksin covid -19. Kesimpulan dalam penelitian ini yaitu menunjukan bahwa Pengetahuan tentang vaksin covid-19 pada masyrakat di Desa Kalait Minahasa Tenggara Sebagian besar responden dengan Pengetahuan yang kurang baik. Kecemasan pada masyarakat di Desa Kalai Minahasa Tenggara Sebagian besar dengan kategori kecemasan berat. Ada hubungan pengetahuan tentang vaksin covid-19 dengan kecemasan pada masyarakat di Desa Kalait Minahasa Tenggara. Kata Kunci : Covid-19, Pengetahuan, Kecemasan ABSTRACT Novel Coronavirus 2019 (2019-nCoV) was officially named as Severe Acute Respiratory Syndrome-Coronavirus 2 (SARS-CoV-2) on 12 February 2020 by the International Committee on Taxonomy of Viruses (ICTV) and on the same day, the World Health Organization (WHO) also declared that the disease caused by SARS-CoV-2 was named as Coronavirus Disease 2019 (COVID-19). WHO designated this disease as a pandemic. The SARS-CoV-2 virus is spread from human to human through respiratory droplets. The Indonesian government has declared the COVID-19 pandemic as a non-natural national disaster, and as an effort to prevent the spread of this virus, the government has implemented several policies, such as limiting activities outside the home, requiring work and online learning, and stopping mass worship activities. Anxiety is a common thing that often occurs in response to environmental changes or distressing events. The purpose of this study was to analyze the relationship between knowledge about the Covid-19 vaccine and anxiety in the community in the village of Kalait, Southeast Minahasa. The type of research used in this research is descriptive analytic with a cross sectional study approach. The population in this study were people aged 18-59 with a sample of 55 respondents. The data were analyzed using the chi square statistical test with a significance level (α): 0.05. Based on the results of the statistical test, the p value of 0.002 is smaller than 0.05, Ha is accepted so that there is a relationship between knowledge about the covid-19 vaccine and anxiety in the community in the village of Kalait, Southeast Minahasa. In this study, the odds ratio was 7.071, which means that poor knowledge has a 7 times chance of experiencing anxiety related to the COVID-19 vaccine. The conclusion in this study is that it shows that knowledge about the covid-19 vaccine in the community in the Kalait Village, Southeast Minahasa, is mostly respondents with poor knowledge. Anxiety in the community in the Southeast Minahasa Kalai Village is mostly in the category of severe anxiety. There is a relationship between knowledge about the covid-19 vaccine and anxiety in the community in the Southeast Minahasa Kalait Village. Keywords: COVID-19, Knowledge, Anxiety Download Full File Disini